A multi-criteria assessment of the p-median, maximal coverage and p-center location models - Karataş, Mümtaz; Razi, Nasuh; Tozan, Hakan (Strojarski Facultet, 2017)
Location problems consider locating facilities with the objective of finding their best locations. In most real world problems, it is common that a demand node is required to be covered with multiple facilities in order to ensure a backup supply. The backup supply is necessary especially for public or emergency service location problems where a covered demand may not be serviced if it's designated facility is engaged serving other demands. In this study we consider three classic location models, i.e. p-median, maximal coverage and p-center, and compare their performances with respect to seven decision criteria under Q-coverage requirement. For this purpose, we generate multiple problem instances and solve each instance with the three models for different Q-values. Our numerical results reveal the pros and cons of each model to assist decision makers in determining the most promising model with respect to each assessment criteria.

Problemi lokacije zna?e lociranje objekata s ciljem pronala?enja najbolje lokacije. Kod ve?ine stvarnih problema uobi?ajeno je da zahtijevani ?vor zadovoljava višestruke uvjete kako bi osigurao rezervnu opskrbu. Ta je rezervna opskrba posebno potrebna kod javnih ili problema lokacije hitne slu?be kada se pokrivena potra?nja ne mo?e osigurati ako je njezin za to odre?eni objekt zauzet pru?anjem usluge drugim zahtijevima. U ovom radu razmatramo tri klasi?na modela lokacije, t.j. p-srednje, maksimalne pokrivenosti i p-centralno, te uspore?ujemo njihovo funkcioniranje u odnosu na sedam kriterija za donošenje odluke u okviru zahtjeva Q-pokrivenosti (Q-coverage). U tu svrhu generiramo slu?ajeve višestrukih problema i svaki slu?aj rješavamo s tri modela za razli?ite Q vrijednosti. Naši numeri?ki rezultati otkrivaju argumente za i protiv svakog modela koji poma?u u donošenju odluke o odre?ivanju modela koji bi najviše odgovarao u odnosu na svaki od kriterija koji se uzimaju u obzir pri donošenju procjene.
Višekriterijska procjena modela lokacije p-srednje, maksimalne pokrivenosti i p-centralno
WOS: 000412257500023
Keywords: Backup Coverage; Facility Location; Maximal Coverage; P-Center; P-Median; Lokacija Objekta; Maksimalna Pokrivenost; P-Centralno; P-Srednje; Rezervna Pokrivenost